INFLUENCE OF ALTERNARIA SPP. FUNGI METABOLITES ON DEVELOPMENT OF WHEAT SPROUTS - Rukavitsina , I.V.; Nelis , O.V.; Bulgakova , I.N. (Eurasian Journal of Applied Biotechnology, 2024)
The study purpose was in vitro investigation of phytotoxic activity of culture broth filtrates (CBFs) of five Alternaria Spp. fungi isolates on development of wheat sprouts. Fungi isolates were received from wheat seeds cultivated under conditions of Northern Kazakhstan. According to the study findings, culture filtrates of all the isolates studied varied with regard to their influence on wheat sprout development. Stimulant effects on seed germinating power were revealed with 14- and 21-day CBFs of A. infectoria (7/4), 14-day CBF of A. brassicae (7/2) and 21-day CBF of A. porri (8/1). It was found that long-term cultivation of fungi on a culture medium contributed to media pH modification towards alkalization due to production of metabolites of various chemical nature, including toxins, which could trigger growth inhibition of radicles and sprouts. However, the CBFs were predominantly low-toxic or non-toxic. Under effect of the 14-day CBF, significant positive correlation was identified between pH values and sprout lengths (0,86±0,25), while negative correlation was found between pH values and germinating power (-0,75±0,33). Change of pH value on the 21st day significantly affected radicle length (-0,92±0,20). Based on the findings it can be concluded that the 14-day CBF of all the Alternaria fungi isolates studied was most toxic for wheat sprouts.